STYLISTIC ANALYSIS OF DAN BROWN’S THE DA VINCI CODE AND ITS RUSSIAN AND UZBEK TRANSLATIONS - Komilova E’zozxon Muhiddinovna; Xudayqulov Abdulla Eshquvatovich (American Journals, 2025)
This paper investigates how key literary devices in Dan Brown’s The Da Vinci Code – such as metaphors, symbolism, allusions, idioms, and wordplay – are rendered in the original English and in the canonical Russian and Uzbek translations. We conduct a comparative stylistic analysis of representative examples (e.g. idiomatic phrases and symbolic references), examining the translation strategies used and the challenges posed by linguistic and cultural differences. Findings show that both Russian and Uzbek translators employ extensive paraphrase and explanatory techniques to convey Brown’s colloquial, reference-heavy style. Idioms are often translated periphrastically or omitted, and complex concepts like the “Holy Grail” require cultural adaptation. Wordplay (e.g. the famous Latin anagram “O Draconian devil! Oh, lame saint!”) cannot be preserved and is typically glossed or left in the source language. The analysis underscores the tension between preserving authorial effect and ensuring comprehension for target readers, reflecting theories of functional equivalence and culturally-aware translation practice.
Keywords: Literary Devices, Stylistic Peculiarities, Translation Challenges, Dan Brown, The Da Vinci Code, English-Russian-Uzbek Translation, Comparative Stylistic Analysis, Idioms and Colloquialisms, Metaphor and Symbolism, Cultural Adaptation, Functional Equivalence, Domestication and Foreignization, Wordplay Translation.